MAGNETIC METHODS IN UNCONVENTIONAL HYDROCARBON EXPLORATION: SETTING THE OBJECTIVES - Menshov, O.; Karpenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper deals with unconventional hydrocarbons exploration and production. Unconventional gas and oil include hydrocarbons in tight rocks, coal bed methane, shale gas and oil. The focus is on magnetic methods in geological exploration and geophysical research on unconventional oil and gas deposits. Oil and gas genesis has no direct bearing on the use of magnetic methods, with the latter being applied directly in hydrocarbon prospecting. On the other hand, an anomalous magnetic signal from soils is comparable in its intensity and amplitude with magnetic signals from hydrocarbon deposits. We have assessed the prospects of developing a direct method of oil and gas exploration based on the assumption that hydrocarbon migration brings about changes in magnetic minerals within the lithological formations of a hydrocarbon halo along the entire oil travel path from the lower geological layers up to the near surface geological section and soils. A correlation has been found between hydrocarbon deposits and changes in magnetic mineralogy caused by hydrocarbon fluid migration. The main magnetic attributes under study include magnetic susceptibility, frequency dependence magnetic susceptibility, isothermal remanent magnetization, saturation magnetization, and the parameters of thermomagnetic analysis. Hydraulic fracturing, which is commonly used to extract hydrocarbons from unconventional reservoirs, often results in emitting environmental pollutants, such as toxic chemical reagents, petroleum derivatives and sand fraction. Furthermore, hydrocarbon handling entails the risk of accidental release of pollutants and contaminating the subsurface, geologic sections, groundwater and soil. It has been shown that environmental pollution caused by hydraulic fracturing and hydrocarbon handling is associated with formation and introduction of secondary magnetic minerals. Magnetic methods used to detect autogenic magnetic substances are rapid, highly efficient and economically sound.